자아가치 보호전략으로서 숨은 소비의도의 역할에 관한 연구 - 김민지(MinJi Kim); 육혜연(Hyeyeon Yuk) (대한경영학회지, 2024)
소비자는 특정 상품을 구매함으로써 긍정적인 자아 이미지를 형성하거나 자신이 겪고 있는 소비 문제를 해결하는 등 접근 동기에서 소비를 하지만, 자신이 소비하는 상품이 타인에게 부정적으로 평가되거나 자아 이미지에 부정적인 영향을 미칠 때는 타인과 거리를 두고자 하는 회피 동기가 생길 수 있다. 소비자가 자신의 소비 목적을 달성하려는 상황에서 자아가치의 훼손이 우려될 때, 타인에게 자신의 소비를 공개하지 않음으로써 자아가치를 보호할 수 있다. 본 연구는 소비자가 자신의 소비행동을 타인에게 공개하지 않으려고 하는 심리적 기제를 파악하여, 소비자 행동을 다면적으로 이해하는데 목적이 있다. 구체적인 연구내용은 다음과 같다. 첫째, 숨은 소비의도에 영향을 미치는 요인으로 자아손상화와 거절민감성을탐색하였다. 둘째, 자아손상화에 영향을 미치는 요인으로 귀인성향 및 타인의 부정적 평가에 대한 두려움을 탐색하였다. 셋째, 제품유형에 따라 각 변수에 차이를 지각하는지 살펴보았다. 연구목적을 달성하기 위해 2023년 10월 31일부터 2024년 4월 5일까지 온라인으로 자료를 수집하여 총 394부를 최종분석에 사용하였으며, 실증분석을 위해 SPSS 25.0의 회귀분석 및 T-Test를 실시하였다. 연구결과, 자아손상화가 숨은 소비의도에 정(+)의 영향을 미치고, 외적귀인성향과 평가두려움이 자아손상화에 정(+)의 영향, 내적 귀인성향은 부(-)의 영향을 미치는 것으로 나타났다. 추가적으로, 숨은 소비의도는 사치품보다 필수품의 구매에서 더욱 커지는 것으로 나타났다. 소비자는 자신이 구매한 제품이 자아 이미지를 긍정적으로 표현해주지 못하는 등의 실패상황에서, 자아가치를 보호하기 위해 자아손상화 전략을 활용할 수 있다. 또한 자신이 구매하는 제품이 자신의 소비목적을 달성시키는 중요한 것이라면, 비공개적 소비를 통해 목적을 달성하면서 자존감을 유지할 수 있다. 자아손상화와 비공개적 소비의 근본적인 이유는 실패에 대한 두려움 및 자신에 대한 타인의 관찰과 평가에 있기 때문에, 외적 귀인성향과 평가두려움을개인의 소비생활에서 자아가치를 보호하는 중요한 요인으로 설명할 수 있다. 본 연구는 소비자가 제품을 소비하는 방법에 대한 새로운 통찰력을 제공하고 고객관계 관리에 관한 방안을 제시할수 있다. 자신의 프라이빗한 소비가 타인에게 공개되어 부끄러움이나 수치심 같은 부정적인 감정을 자주 느끼게 되면, 해당 제품이나 기업에게 감정이 전이되어 기업과 소비자 간의 관계에 부정적인 영향을 미칠 수 있다. 따라서 마케팅 관리자는 타깃 소비자들이 자신의 구매행동을 공개하지 않으려고 할 경우, 자사제품의 특성과 개인 소비자의 성향을 깊이 이해하고 분석하여 소비자들의 구매행동이 공개되지 않도록 유통채널을 구축하거나 개인정보보안과 같은 전략을 수립하고 실행해야 할 것이다. Consumers engage in consumption for various reasons, such as creating a positive self-image or solving consumption problems. However, when the products they consume are negatively evaluated by others or have a negative impact on their self-image, they may experience a desire to avoid social interactions. When consumers fear that their self-worth may be damaged in the process of achieving their consumption goals, they may protect their self-worth by concealing their consumption from others. This study aims to understand the psychological mechanisms underlying consumers' reluctance to disclose their consumption behavior to others, thereby providing a multi-faceted understanding of consumer behavior. Specifically, this study investigated the factors influencing the intention to hidden consumption, such as self-handicapping and rejection sensitivity. Furthermore, it explored the factors influencing self-handicapping, including attributional style and fear of negative evaluation. Finally, it examined whether there were differences in each variable across product types. To achieve the research objectives, online data were collected from October 31, 2023, to April 5, 2024, and a total of 394 responses were used for the final analysis. Regression analysis and T-tests were conducted using SPSS 25.0 for empirical analysis. The results showed that self-handicapping had a positive effect on the intention to hidden consumption, and external attribution and fear of evaluation had a positive effect on self-handicapping, while internal attribution had a negative effect. Additionally, the intention to hidden consumption was found to be greater for the purchase of essential goods than luxury goods. Consumers may use self-image threat strategies to protect their self-worth when they fail to positively represent their self-image through the products they purchase. Furthermore, if the products they purchase are important for achieving their consumption goals, they can maintain their self-esteem by achieving their goals through non-public consumption. Since the underlying reasons for self-handicapping and hidden consumption are fear of failure and others' observations and evaluations of oneself, external attribution and fear of evaluation can be explained as important factors in protecting one's self-worth in consumption life. This study provides new insights into how consumers consume products and offers implications for customer relationship management. If consumers frequently feel negative emotions such as embarrassment or shame when their private consumption is revealed to others, these negative emotions may transfer to the products or companies involved, negatively affecting the relationship between the company and the consumer. Therefore, marketing managers should deeply understand the characteristics of their target consumers' products and individual preferences, and develop strategies such as building distribution channels that prevent consumers from disclosing their purchasing behavior or establishing personal information security measures when consumers are reluctant to disclose their purchasing behavior. KCI Citation Count: 0